Time resolution of the plastic scintillator strips with matrix photomultiplier readout for J-PET tomograph. (19th February 2016) - Moskal, P; Rundel, O; Alfs, D; Bednarski, T; Białas, P; Czerwiński, E; Gajos, A; Giergiel, K; Gorgol, M; Jasińska, B; Kamińska, D; Kapłon, Ł; et al.
Abstract: Recent tests of a single module of the Jagiellonian Positron Emission Tomography system (J-PET) consisting of 30 cm long plastic scintillator strips have proven its applicability for the detection of annihilation quanta (0.511 MeV) with a coincidence resolving time (CRT) of 0.266 ns. The achieved resolution is almost by a factor of two better with respect to the current TOF-PET detectors and it can still be improved since, as it is shown in this article, the intrinsic limit of time resolution for the determination of time of the interaction of 0.511 MeV gamma quanta in plastic scintillators is much lower. As the major point of the article, a method allowing to record timestamps of several photons, at two ends of the scintillator strip, by means of matrix of silicon photomultipliers (SiPM) is introduced. As a result of simulations, conducted with the number of SiPM varying from 4 to 42, it is shown that the improvement of timing resolution saturates with the growing number of photomultipliers, and that the configuration at two ends allowing to read twenty timestamps, constitutes an optimal solution. The conducted simulations accounted for the emission time distribution, photon transport and absorption inside the scintillator, as well as quantum efficiency and transit time spread of photosensors, and were checked based on the experimental results. Application of the matrix of SiPM allows for achieving the coincidence resolving time in positron emission tomography of 0.170 ns for 15 cm axial field-of-view (AFOV) and 0.365 ns for 100 cm AFOV. The results open perspectives for construction of a cost-effective TOF-PET scanner with significantly better TOF resolution and larger AFOV with respect to the current TOF-PET modalities.